Transpancreatic precut papillotomy versus double-guidewire technique in difficult biliary cannulation: a systematic review and meta-analysis - Edson Guzmán-Calderón (Georg Thieme Verlag KG, 2021)
Background and study aims Approximately 11 % of biliary cannulations are considered difficult. The double guidewire (DGW-T) and transpancreatic sphincterotomy (TPS) are two useful techniques when difficult cannulation exists and the main pancreatic duct is unintentionally accessed. We carried out a systematic review and meta-analysis to evaluate the effectiveness and security of both DGW-T and TPS techniques in difficult biliary cannulation. Methods We conducted a systematic review in different databases, such as PubMed, OVID, Medline, and Cochrane Databases. Were included all RCT which showed a comparison between TPS and DGW in difficult biliary cannulation. Endpoints computed were successful cannulation rate, median cannulation time, and adverse events rate. Results Four studies were selected (4 RCTs). These studies included 260 patients. The mean age was 64.79 ± 12.99 years. Of the patients, 53.6 % were men and 46.4 % were women. The rate of successful cannulation was 93.3 % in the TPS group and 79.4 % in the DGW-T group (P = 0.420). The rate of post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP) was lower in patients who had undergone TPS than DGW-T (TPS: 8.9 % vs DGW-T: 22.2 %, P = 0.02). The mean cannulation time was 14.7 ± 9.4 min in the TPS group and 15.1 ± 7.4 min with DGW-T (P = 0.349). Conclusions TPS and DGW are two useful techniques in patients with difficult cannulation. They both have a high rate of successful cannulation; however, the PEP was higher with DGW-T than with TPS.